An Analysis of the Role of Verbal and Nonverbal Communication in Preventing Misunderstandings in Social Interactions in the Digital Era - Naila nurrahmi; MAZATUL AKMA; Annisa Lestari Pohan; Riza Aprianti; Darmawati (Jurnal Ilmu Komunikasi Balayudha, 2026)
This investigation seeks to explore the significance of both verbal and nonverbal communication in minimizing misinterpretations in interpersonal exchanges within the digital age. The impetus for this research stems from the considerable likelihood of misunderstandings in text-based communication, stemming from the lack of immediate emotional cues. This study employs a qualitative methodology through interviews conducted with 10 participants aged between 18 and 20 years. The data collected were examined by means of data reduction, presentation of findings, and formulating conclusions. reduction, data presentation, and conclusion drawing. The findings indicate that straightforward, uncomplicated, and direct verbal interactions are essential in reducing confusion. Furthermore, nonverbal aspects like emojis and audio messages assist in expressing feelings and elucidating the purpose of messages. Misinterpretations frequently arise from variances in understanding that stem from the lack of tone and facial cues. As a result, people generally opt for more transparent communication methods, such as phone conversations, to clear up misunderstandings. In summary, spoken and unspoken forms of communication work together to enhance effective online interactions. The skill to handle both elements and grasp the context of communication is crucial for minimizing misinterpretations.